Model of Competency Development for Accounting Students: Case Study: Auditing Course - Afni, Zalida; Haryadi, Anda Dwi (The International Journal of Business Review (The Jobs Review), 2024)
This study aims to identify relevant competencies for accounting students in auditing and design a relevant learning model to face the disruption era. This research uses a survey method with a descriptive quantitative approach. The selection sample technique in this study used purposive sampling technique involving practitioners in the fields of accounting, finance and auditing. The results showed that the relevant competencies for accounting students in the field of auditing in accordance with industry needs are intellectual, technical and functional, organizational and management, interpersonal and communication, and personal competencies. Meanwhile, the design of the learning model in this study is based on learning methods that are relevant to universities and in accordance with industry needs. The learning methods used are lectures, group discussions, and cooperative learning for Audit Fundamentals, group discussions and simulations for Advanced Audit, case-based learning and project-based learning for Audit Practicum.